Study of Oxygen Vacancies on Different Facets of Anatase TiO2. Issue 9 (31st July 2019) - Wu, Yanan; Fu, Yingyi; Zhang, Li; Ren, Yuanhang; Chen, Xueying; Yue, Bin; He, Heyong
Summary of main observation and conclusion: Anatase TiO2 samples with different ratios of 101 to 001 facets were prepared with hydrothermal method and further treated under three specific calcination atmospheres (air, H2, N2 ). The characterization results indicate that 001 facets may generate more oxygen vacancies and more Ti 3+ species than 101 facets. Abstract : Oxygen vacancies are easier to form on 001 facets than on 101 facets of anatase TiO2 .